2015
DOI: 10.1080/08961530.2015.1014281
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Global Consumer Culture and National Identity and the Effect on Japanese Consumer Behavior

Abstract: Acculturation research has mostly focused on the experiences of ethnic minorities, but nowadays global forces are shaping mainstream societies. How does exposure to global consumer culture (GCC) combine with a social identity drawing from nationality to impact consumer behavior? Using multidimensional measures for national ethnic identity and acculturation to GCC (AGCC), we investigate cultural relationships with an array of consumer attitudes and behaviors, focusing on Japan: an economically advanced country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 64 publications
3
53
0
Order By: Relevance
“…Dmitrovic et al (2009) further emphasize that in order to understand ethnic consumption behaviour, research needs to investigate the "growing impact of consumers' national and ethnic identities on their consumption motivations" and "the complexity of consumers' choice between locally produced goods and their imported alternatives" (p. 524). As distinct from ethnic identity, which emphasizes one's affiliation with an ethnic group (Pires et al, 2003), national identification, which refers to a connection with a specific place where individuals share a common set of rights and duties (He & Wang, 2015), and its impact on consumption behaviours, has also been studied extensively for groups ranging from Canadians and Chileans (Cleveland, Rojas-Méndez, Laroche, & Papadopoulos, 2016) to Japanese (Cleveland, Laroche, & Takahashi, 2015) and immigrants in general (Bardhi, Eckhardt, & Arnould, 2012).…”
Section: Consumer Ethnicity and Ethnic Identitymentioning
confidence: 99%
“…Dmitrovic et al (2009) further emphasize that in order to understand ethnic consumption behaviour, research needs to investigate the "growing impact of consumers' national and ethnic identities on their consumption motivations" and "the complexity of consumers' choice between locally produced goods and their imported alternatives" (p. 524). As distinct from ethnic identity, which emphasizes one's affiliation with an ethnic group (Pires et al, 2003), national identification, which refers to a connection with a specific place where individuals share a common set of rights and duties (He & Wang, 2015), and its impact on consumption behaviours, has also been studied extensively for groups ranging from Canadians and Chileans (Cleveland, Rojas-Méndez, Laroche, & Papadopoulos, 2016) to Japanese (Cleveland, Laroche, & Takahashi, 2015) and immigrants in general (Bardhi, Eckhardt, & Arnould, 2012).…”
Section: Consumer Ethnicity and Ethnic Identitymentioning
confidence: 99%
“…First, this research adds to our understanding of the dynamics behind the formation of materialistic and consumer ethnocentric attitudes among millennials. Second, it examines the impact of globalization on consumer culture as the interaction between global and local forces rather than reducing it to the predominance of either one of these forces (Cleveland, Laroche, & Takahashi, 2015). Third, the current study answers the call for research focused on the heterogeneity within cultures, in addition to the heterogeneity found between cultures.…”
mentioning
confidence: 80%
“…However, a lack of studies exists exploring the determinants of these two attitudinal outcomes in depth as well as comparing this process across cultures. Furthermore, a number of investigations have called for research to focus on the interaction between consumers' local and global contexts, rather than determining which force predominates (Berry, 2008;Cleveland et al, 2015). Only a few studies address materialism and consumer ethnocentrism among millennials (Bevan-Dye, Garnett, & de Klerk, 2012; Kim & Jang, 2017) and none of them focus on the determinants of these two attitudes within millennials' global and national identity components.…”
Section: Millennials' Consumer Identitiesmentioning
confidence: 99%
“…But conversion of the understanding of consumption-related symbols and behaviours into actual consumption behaviour also depends on consumers' own local meaning systems (Akaka & Alden, 2010;Alden, Steenkamp, & Batra, 1999), influencing which effects on consumer behaviour are driven by the global and local cultures, as well as the final outcome of the dual effects (Cleveland, Laroche, & Takahashi, 2015). GCC involves an ongoing acculturation process that might entail different things in different countries (Cleveland & Laroche, 2007), such that it may take time and continued enquiry for GCC to be fully understood.…”
Section: Introductionmentioning
confidence: 99%